Actors, Institutions, and the Making of EU Gender Equality Programs - Ahrens, Petra (Gender and Politics,, 2018)
This book is an actor-centred sociological study of the EU-level processes that produce gender equality policy. Based on interviews and documentary analysis, the study unpacks the process of the "Roadmap for Equality between Women and Men 2006-2010" to explain the different roles of actors in the making of EU gender equality policies. By analysing policy processes inside institutions and among institutions, the study focuses on the internal working logics in and between EU-level institutions. It highlights the shifting spaces, openings, and constraints for the development of gender equality policies. Concentrating on EU policy programmes helps shed light on the invisible aspects of EU gender equality policy-making and how this process changed regarding actors, structure and content in the late 2000s. This book will be of interest to students and scholars in the fields of EU politics, gender politics, and public policy, as well as to institutional and non-governmental actors in the area of gender politics in Europe and the working of EU politics.